2004
DOI: 10.1377/hlthaff.var.33
|View full text |Cite
|
Sign up to set email alerts
|

Who You Are And Where You Live: How Race And Geography Affect The Treatment Of Medicare Beneficiaries

Abstract: There is no simple story that explains the regional patterns of racial disparities in health care.by Katherine Baicker, Amitabh Chandra, Jonathan S. Skinner, and John E. Wennberg ABSTRACT: The existence of overall racial and ethnic disparities in health care is well documented, but this average effect masks variation across regions and types of care. Medicare claims data are used to document the extent of these variations. Regions with high racial disparities in one procedure are not more likely to be high in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
177
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(185 citation statements)
references
References 17 publications
7
177
1
Order By: Relevance
“…Previous research has shown that where a patient lives can affect the level and quality of health care the patient receives independent of individual characteristics, and that overuse patterns do not differ by insurance type. [12][13][14][15] Recent evidence indicates provider organizations and regions with a higher proportion of primary care physicians have lower utilization and spending and better use of recommended preventive and chronic care. 1 6 Moreover, workforce characteristics explain 42% of the state-level variation in Medicare spending per beneficiary.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that where a patient lives can affect the level and quality of health care the patient receives independent of individual characteristics, and that overuse patterns do not differ by insurance type. [12][13][14][15] Recent evidence indicates provider organizations and regions with a higher proportion of primary care physicians have lower utilization and spending and better use of recommended preventive and chronic care. 1 6 Moreover, workforce characteristics explain 42% of the state-level variation in Medicare spending per beneficiary.…”
Section: Discussionmentioning
confidence: 99%
“…In interpreting the findings of our analysis, considerations need to be given to the inherent limitations of the data analyzed. Information in the Medicare database is prone to bias due to inaccuracy of claims coding for specific diagnoses [80][81][82][83]. In an attempt to reduce misclassification for outcomes of interest, we used primary and secondary diagnosis codes to identify records for inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 The finding that the percentage of provider-attributable and tumor characteristics as well as surgeon nephrectomy case volume (the residual intraclass correlation coefficient). The denominator for calculation of this proportion includes the residual variance attributable to the surgeon random effect (after adjustment for patient demographics, comorbidity, tumor size, and surgeon case volume) and the variance attributable to unmeasured patient or tumor variables plus error.…”
Section: Discussionmentioning
confidence: 99%